In Vitro Anti-Inflammatory Activity of the Root of Thottea siliquosa (Lam.) Rottb., a Medicinal Undershrub in Western Ghats, India: Life Sciences-Botany for Medicinal science - P.N.b, Shaiju; M, Athira; S.R., Suja (International Journal of Life Science and Pharma Research, 2021)
Inflammation can be considered as an essential immune response that helps the body to survive during the conditions of infection and injury. Drugs for curing inflammation had their origin in the accidental discovery of certain plants and their extracts being used for relief of pain, fever and anti-inflammation. Since the plants are considered as the first source of remedies for ailments in human history, a large number of plants were used as drugs against all kinds of ailments through all ages. Thottea siliquosa, commonly known as ‘Alpam’ belongs to the family Aristolochiaceae is a medicinal undershrub, the crude root extracts of which are widely used in traditional tribal healthcare systems in the slopes of the Western Ghats, India, for treating inflammatory responses. The present study is an attempt to scientifically validate this ethnic practice. Root extracts of T. siliquosa were prepared using solvents like chloroform, ethyl acetate, 70% ethanol, methanol, and distilled water by soxhlet mode of extraction. Anti-inflammatory responses in different solvent extracts were analyzed by albumin denaturation assay, anti-protease assay, Human red blood cell membrane stabilization assay (HRBC method), Cyclooxygenase (COX), and Lipoxygenase (LOX) assays. RAW 264.7 cell lines were used for the COX and LOX study. The results illustrate the antiinflammatory potential of the root extracts. The studies on cell lines clearly indicated that the higher anti-inflammatory potential of chloroform extract over other solvent extracts. In tune with the ethno-botanic information, the aqueous extract offered a dose-dependent anti-inflammation property. Since most of the bio activity of plant extracts are contributed by the phytochemicals present in it, further efforts shall be made for the isolation and purification of bioactive phyto components responsible for the anti-inflammation property of the T. siliquosa root.